Evaluation of Arterial Stiffness for Predicting Future Cardiovascular Events in Patients with ST Segment Elevation and Non-ST Segment Elevation Myocardial Infarction. (30th October 2013) - Akkus, Oguz; Sahin, Durmus Yildiray; Bozkurt, Abdi; Nas, Kamil; Ozcan, Kazım Serhan; Illyés, Miklós; Molnár, Ferenc; Demir, Serafettin; Tüfenk, Mücahit; Acarturk, Esmeray
Abstract : Background . Arterial stiffness parameters in patients who experienced MACE after acute MI have not been studied sufficiently. We investigated arterial stiffness parameters in patients with ST segment elevation (STEMI) and non-ST segment elevation myocardial infarction (NSTEMI). Methods . Ninety-four patients with acute MI (45 STEMI and 49 NSTEMI) were included in the study. Arterial stiffness was assessed noninvasively by using TensioMed Arteriograph. Results . Arterial stiffness parameters were found to be higher in NSTEMI group but did not achieve statistical significance apart from pulse pressure ( P = 0.007 ) . There was no significant difference at MACE rates between two groups. Pulse pressure and heart rate were also significantly higher in MACE observed group. Aortic pulse wave velocity (PWV), aortic augmentation index (AI), systolic area index (SAI), heart rate, and pulse pressure were higher; ejection fraction, the return time (RT), diastolic reflex area (DRA), and diastolic area index (DAI) were significantly lower in patients with major cardiovascular events. However, PWV, heart rate, and ejection fraction were independent indicators at development of MACE. Conclusions . Parameters of arterial stiffness and MACE rates were similar in patients with STEMI and NSTEMI in one year followup. The independent prognostic indicator aortic PWV may be an easy and reliable method for determining the risk of future events in patients hospitalized with acute MI.